1986
DOI: 10.1002/jcu.1870140408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of renal calcification in infants on chronic furosemide therapy

Abstract: We describe seven infants who developed renal calcification and bone demineralization following furosemide therapy with average daily doses of as little as 0.75 mg/kg per day. Renal calcifications were present in all seven cases and were more readily detected with ultrasonography than with plain films. Renal calculi were seen in four patients, sonographically demonstrated as echogenic foci in the dependent portion of the collecting system, usually accompanied by acoustic shadowing. One patient developed nephro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Reports from North America have established the association of frusemide therapy and nephrocalcinosis in very low birth weight infants [1][2][3][4][5]. These babies had at least 10 days frusemide treatment, and usually 3 weeks or more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from North America have established the association of frusemide therapy and nephrocalcinosis in very low birth weight infants [1][2][3][4][5]. These babies had at least 10 days frusemide treatment, and usually 3 weeks or more.…”
Section: Discussionmentioning
confidence: 99%
“…Other American authors have since described the radiographic and sonographic findings of frusemide induced nephrocalcinosis [2][3][4][5]. To our knowledge, no similar reports have been published in Britain.…”
mentioning
confidence: 97%
“…Several authors have noted this complication with a variable frequency [5][6][7][8][9][10]. In a large review o f the literature, Adams and Rowe [29] point-ed out that, in most cases, specific clinical or biological or therapeutic circumstances cannot be found, and that it is im possible to incriminate a sole cause in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent administration of parent eral nutrition has been incriminated by several authors [4,5,8,9], but this was not observed in all cases. Because of the lack of specific standards for preterm infants, we used the normal values of oxalate excretion for children proposed by Barratt [23] and the ratio recommended by Leumann ct al.…”
Section: Discussionmentioning
confidence: 99%
“…These calcium oxalate deposits may be identified on plain films of the abdomen but are more readily detected by ultrasound. 1,2 Estimates of the incidence of nephrocalcinosis in premature infants have varied considerably. Jacinto et al 3 have reported a 65% incidence of nephrocalcinosis, whereas Short and Cooke 4 reported a 27% incidence in very low birth weight infants.…”
mentioning
confidence: 99%